Pengaruh Manajemen Pengetahuan Dan Pembelajaran Organisasi Terhadap Inovasi Serta Dampaknya Terhadap Keunggulan Bersaing PT. Bank Riau Kepri - Nova Pradana Nasution; Zulfadil Zulfadil; Deny Setiawan (Akuntansi & Ekonomika, 2021)
This study aims to determine the effect of knowledge management and organizational learning on innovation and it’s impact on competitive advantage of PT. Bank Riau Kepri. This study took a sampel of 80 people consisting of 20 office unit leaders and 60 section leaders from 20 branch office units. The variables used are knowledge management, organizational learning, innovation and competitive advantage. Data analysis was performed using path analysis with the help of SPSS 22 program. The results showed that there was a direct significant influence on knowledge management and organizational learning on innovation as well as on competitive advantage and there was a significant influence on innovation on competitive advantage. Indirectly, there is a significant effect on knowledge management and organizational learning on competitive advantage through innovation.